Justice in transactions a theory of contract law - Benson, Peter, 1953- (The Belknap Press of Harvard University Press, 2019)
This book seeks to provide a moral basis for contract law that can not only make sense of its main doctrines in their own terms but also bring out the distinct conception of justice that actually animates them. The author shows in detail that this conception of justice is purely transactional and non-distributive in character but at the same time that it fits within a larger framework of liberal justice that includes robust principles of distributive justice such as Rawls's. Even though the focus of the work is on the common law of contract, the proposed theory bears on the justification of modern contract law in other legal traditions as well, such as the civil law.--